(untitled) (Journal of International Studies, 2020)
Once considered the internal domain of states, of late human rights issues and concerns have been frequently raised at the international level through the use of human rights diplomacy. However, human rights diplomacy is not only confined to like-minded states who often raise issues pertaining to human rights violations abroad, but can also employed by states violating human rights as a means for its own defence. Under intense criticism for its abysmal human rights record, the Myanmar regime too has often resorted to human rights diplomacy as a strategy to deflect criticism, mainly from without. In doing so, the regime not only often invokes the notion of sovereignty, but even undertakes systematic attacks on the members of the international media and transnational advocacy groups who raise these issues. In addition and knowing that these issues have often dented its own credibility and legitimacy, the Myanmar junta even embarked on an image-building campaign, namely by enlisting the services of foreign public relations firms. In the light of these developments, this article will analyse how Myanmar’s military regime has used defensive human rights diplomacy to ward-off criticism against its poor human rights record.